The impact of the Covid-19 pandemic on outpatient visits for patients with cancer in Iran: an interrupted time series analysis - Siavash Beiranvand; Meysam Behzadifar; Aidin Aryankhesal; Seyed Jafar Ehsanzadeh; Banafshe Darvishi Teli; Masoud Behzadifar (Archives of Public Health)
Abstract Background The Covid-19 pandemic has posed unprecedented challenges to healthcare systems worldwide, affecting routine medical services, including for cancer patients. This study investigates the impact of the Covid-19 pandemic on outpatient visits for patients with cancer in Iran. Methods We conducted an interrupted time series analysis (ITSA) on data collected from electronic medical records. The ITSA methodology was employed to analyze monthly outpatient visits for patients with cancer data from March 2017 to January 2023 in Lorestan University of Medical Sciences. Results Following the announcement of Covid-19 in Iran, outpatient visits for patients with cancer decreased immediately and sharply, with a mean of 247.08 visits per month, which has a 95% confidence interval of [-297; -197]. Subsequent waves in June 2020, September 2020, April 2021, July 2021, and January 2022 further affected outpatient visits. However, the initiation of Covid-19 vaccination, particularly for cancer patients, marked a positive turning point, leading to an increase of 156.39 outpatient visits between January and February 2022. Conclusion Our study provides critical insights into the dynamic relationship between the Covid-19 pandemic, patient behavior, and cancer care utilization. The observed decrease in outpatient visits underscores the multifaceted challenges faced by cancer patients during the pandemic, while the positive influence of vaccination signals a pathway towards recovery. The importance of vaccination is highlighted as a key factor in improving outpatient visit rates. As healthcare systems adapt to ongoing challenges, understanding the complex interplay between public health crises and patient behavior is crucial for shaping resilient and patient-centric healthcare systems.